Flexible and cross-linked N-doped carbon nanofiber network for high performance freestanding supercapacitor electrode - Cheng, Yongliang; Huang, Liang; Xiao, Xu; Yao, Bin; Yuan, Longyan; Li, Tianqi; Hu, Zhimi; Wang, Bo; Wan, Jun; Zhou, Jun (Nano energy, 2015)
Flexible, cross-linked N-doped carbon nanofiber network (CLCF) is successfully prepared via electrospinning and carbonization process. CLCF shows a specific capacitance of 175F/g at the current density of 50A/g with an excellent rate capability of 78.5% of its initial capacitance from 0.5A/g to 50A/g under the mass loading of 1.2mg/cm2. Supercapacitor device based on CLCF exhibits high energy density of 5.9Wh/kg with a power density of 1200W/kg, as well as excellent cycling stability which achieves 106% capacitance retention after 20,000 charge–discharge cycles. Solid-state supercapacitor device displays outstanding mechanical flexibility and no obvious capacitance loss can be observed even when the device was bended to 180°. Moreover, as scaffold for supporting PANi, capacitance retention of CLCF/PANi can reach 72% with the current density range from 0.5 to 50A/g. All the results suggest that CLCF has great potential for application not only as supercapacitor electrode but also as scaffold for supporting capacitive materials. [Display omitted] •Flexible, cross-linked N-doped carbon nanofiber network has been successfully prepared via electrospining and carbonization process.•The cross-linked carbon nanofibers shows a specific capacitance of 175F/g with an excellent rate capability and cycling stability.•The cross-linked carbon nanofibers can served as effective scaffold for supporting capacitive materials.